Cryptocurrency and Asset Recovery in Bankruptcy: An Interdisciplinary Legal-Accounting Approach - Wibowo, Benedictus Satryo; Ananda Sabrida Tora Boru Sinaga, Ananda Sabrida Tora Boru Sinaga (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The increasing adoption of cryptocurrency in Indonesia poses legal and technical challenges in bankruptcy proceedings due to the absence of comprehensive regulation. This research aims to analyze the legal status, valuation mechanisms, and asset recovery of cryptocurrency in bankruptcy from an interdisciplinary legal-accounting approach. Using normative juridical methods and literature studies, the findings show that cryptocurrency's decentralized nature complicates identification and control, while regulatory inconsistencies between authorities exacerbate legal uncertainty. Forensic accounting is essential for asset tracing and valuation, yet lacks standardized frameworks. The study concludes that legal reforms and the integration of legal and accounting expertise are vital for effective management of digital assets in insolvency.